"Efecto de cinco niveles de fósforo y carbonato de calcio en la producción de materia seca, extracción de fósforo en cebada (Hordeum vulgare L.) y su disponibilidad de fósforo en el suelo, bajo condiciones de invernadero - León Perez, Saida Liz (2012)
Thepresent researchwas conductedin November 2005to February 2006, at the Faculty of Agricultura Sciences atthe National University offrujillolocatedin the District offrujillo,Province offrujillo, La LibertadDepartment.The research work aimed at determining the "Effect of five levels of phosphorus and calcium carbonate in dry matter production, extraction of phosphorus in barley (HordeumvulgareL.) and its availability in the soil, under greenhouse conditions. Experimental design was used in a randomized complete block with factorial of 5 for 5 with 4 replications. The treatments used were interaction ofO, 4, 8, 16 and 32% calcium carbonate with O, 20, 40, 60 and 80 ppm of phosphorus, making a total of 25 treatments. Statistical analysis was analysis of varían ce and Duncan test of significance of 5%.The results showed that if there is an effect on the interaction of phosphorus and calcium carbonate in the production of dry matter and the concentration of phosphorus in the floor, but not in the phosphorus availability in soil, this effect being the result of factors: calcium carbonate and phosphorus independently